Erratum: Neoteric FT-IR investigation on the functional groups of phosphonium-based deep eutectic solvents (Spectrochim. Acta Part A: Mol. Biomol. Spectrosc. (2015) 149 (588-591) DOI: 10.1016/j.saa.2015.05.001 PII: S1386142515005892) - Aissaoui, T. (Elsevier B.V., 2015)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy). The journal Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy retracts the article "Neoteric FT-IR investigation on the functional groups of phosphonium-based deep eutectic solvents" by Aissaoui Tayeb et al., which was published in 2015. This retraction comes after a thorough and time-consuming analysis of the published article, the data it reports and author relationships. The editors deferred making any public statements regarding this article until this investigation was complete, and the authors were notified of the findings. Very shortly after the publications of the article the journal received communications indicating that parts of the manuscript were reused from another publication ("Triethylene glycol based deep eutectic solvents and their physical properties" by Hayyan et al. published in the Journal of the Taiwan Institute of Chemical Engineers in 2015, http://dx.doi.org/10.1016/j.jtice.2015.03.001) and that two out of four authors were not informed nor did they agree with the submission to Spectrochimica Acta Part A. Due to the nature of the concerns raised about this paper, the editors examined the manuscripts and reviewed the responses from the authors. The editors wish to acknowledge the co-operation of all involved parties in this matter, and commend them for their commitment to the scientific process. Ultimately, the editors found considerable overlap and redundancy between the article published in Spectrochimica Acta Part A and the article published in the Journal of the Taiwan Institute of Chemical Engineers. Together with the disagreement of Mohd Ali Hashim and Maan Hayyan with the publication of this article, the editors came to the conclusion to retract the article. Â© 2015 Elsevier B.V.